Racial Differences in Resilience: U.S. College Student’s Mental Health and the COVID-19 Pandemic - Xi, Juan (Race and social problems, 2025)
Concerns about the mental health of college students have been increasing over the last several decades. The COVID-19 pandemic only served to put more attention on this problem. Prior to the pandemic, minority students bore a heavier burden of mental disorder symptoms, but it is unclear if this racial difference persisted during the COVID-19 pandemic and if the resilience of students to this crisis varies by race. This study investigates race-specific trends in college students’ mental health, using four repeated cross-sectional surveys collected yearly between November 2019 and November 2022 from students in a Midwestern state university in the United States. We found that racial minority students had a higher level of symptoms before the pandemic. However, they did not experience a significant elevation during the pandemic. On the other hand, White students reacted more dramatically to the initial shock of the pandemic in 2020. They recovered in 2021 but experienced another elevation in mental health symptoms in 2022. Our study added to the minority mental health paradox literature that racial minority students were more resilient to the impact of the pandemic than White students. Programs to enhance resilience for all students are recommended.